Review Study of Identify Main Factor That Causes the Cracking and Potholes on Asphalt Pavement in Malaysia - Bukhari, Nur Ridzuan; Aman , Mohamad Yusri (Recent Trends in Civil Engineering and Built Environment, 2023)
Abstract: This will destroy the road physically and internally, and it may also risk the safety of road users. In recent years, highway engineering has seen significant growth, necessitating good condition of pavement during the pavement facing the load of traffic heavy loaded vehicle and climate change we will see the change of behavior and condition of pavement Cracks are the common distresses that develop in pavement sector in Malaysia. According to the claim, pavement deterioration will create a dangerous environment for road users, resulting in traffic collisions. If there is a massive pothole on the road, for example, a motorist may strike the potholes. I indicated that excessive rut depth pavement degradation will result in a higher rate of collisions. Pavement care is therefore critical for ensuring safety as well as maintaining and extending the pavement life cycle. Cracking, potholes, bleeding, depression, and other types of road deterioration are examples. second, determine and classify the cause of the road damage and why it occurred on the road’s surface. Many types of study have been conducted on this issue, particularly in Malaysia, such as finding solutions to address roadway damage, study into road damage specifications, and how to prevent road deformation, to name a few. As a result, the problem may be investigated in this study, as well as the primary elements and certain procedures that can be performed to categorize road damage in a systematic and unambiguous manner. in addition to bringing the broader public’s attention to the issue. Keywords: Road, pavement, Malaysia, pothole, road damage, highway,